2016
DOI: 10.1093/cid/ciw038
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics as Antifungals in Mucosal Candidiasis

Abstract: Candida is an opportunistic pathogen that causes mucosal and deep systemic candidiasis. The emergence of drug resistance and the side effects of currently available antifungals have restricted their use as long-term prophylactic agents for candidal infections. Given this scenario, probiotics have been suggested as a useful alternative for the management of candidiasis. We analyzed the available data on the efficacy of probiotics in candidal colonization of host surfaces. A number of well-controlled studies ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 38 publications
1
79
0
11
Order By: Relevance
“…Consequently, there has been an increasing interest in the use of probiotics for oral infections [39], including periodontal diseases. In this systematic review, we attempted to collate the available clinical and microbiological evidence on the utility of probiotics in the management of chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there has been an increasing interest in the use of probiotics for oral infections [39], including periodontal diseases. In this systematic review, we attempted to collate the available clinical and microbiological evidence on the utility of probiotics in the management of chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Initially it was suggested that antibiotic treatment removed lactobacilli from the vaginal mucosa, increasing vaginal pH, and promoting Candida hyphal formation. In agreement with this, lactobacilli have been proposed to reduce Candida colonisation [37], and have been explored as a potential probiotics [38]. However, other studies suggest that vaginal pH, and the lactobacilli population are not significantly altered in VVC [39], and that Candida colonisation is more common in women with a lactobacillus dominated microflora [40].…”
Section: Candida Albicans: the Ubiquitous Fungal Symbiontmentioning
confidence: 99%
“…The probiotics, mainly lactic acid bacteria, are deemed worthy as an alternative prophylactic and therapeutic agent for managing human candidiasis ( Figure 1A and B) [127][128][129]. Although the mechanisms of action of probiotics against Candida is unclear, as yet, the major attribute of probiotics appears to be the restoration of a natural healthy microbiome in a given habitat [129].…”
Section: Probioticsmentioning
confidence: 99%
“…Although the mechanisms of action of probiotics against Candida is unclear, as yet, the major attribute of probiotics appears to be the restoration of a natural healthy microbiome in a given habitat [129]. The re-establishment of a well-balanced and symbiotic state by probiotic bacteria, with suppression of Candida infection, may entail five distinct mechanisms: i) coaggregation of probiotic and fungal cells in order to impedes fungal colonization, ii) production of antagonistic antimicrobial and anti-biofilm compounds, iii) competing with the pathogen for available nutrients and adhesion sites, iv) production of quorum sensing chemicals that lead to down regulation of toxin production by the pathogens, and finally, v) modulation of the humoral and cellular immune system of the host (e.g.…”
Section: Probioticsmentioning
confidence: 99%